2011
DOI: 10.1080/03079457.2011.571659
|View full text |Cite
|
Sign up to set email alerts
|

Investigations into an outbreak of corvid respiratory disease associated withPasteurella multocida

Abstract: The possible cause of disease and mortality in corvids on an outdoor pig unit in the north of England between August 2007 and March 2008 was investigated. Nine carrion crows (Corvus corone corone) and nine rooks (Corvus frugilegus), comprising five live-caught birds with clinical signs of respiratory disease, one live-caught bird without respiratory disease, and 12 birds submitted dead were examined. Clinical signs, gross and histopathological examination, microbiology and toxicology indicated that Pasteurella… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 25 publications
1
9
0
Order By: Relevance
“…In this study, 23 strains of P. multocida isolated from poultry in Chongqing and Sichuan, China were tested for capsular antigens and antimicrobial susceptibility. The results showed that the capsular types of isolates were predominantly type A which is similar to that it was usual reported for P. multocida in China and other countries [34,35] . But we found one isolate of P. multocida was type F which is similar to the findings that reported previously [33] .…”
Section: Discussionsupporting
confidence: 77%
“…In this study, 23 strains of P. multocida isolated from poultry in Chongqing and Sichuan, China were tested for capsular antigens and antimicrobial susceptibility. The results showed that the capsular types of isolates were predominantly type A which is similar to that it was usual reported for P. multocida in China and other countries [34,35] . But we found one isolate of P. multocida was type F which is similar to the findings that reported previously [33] .…”
Section: Discussionsupporting
confidence: 77%
“…gallicida are also sometimes isolated (223). Capsular serotype A (mainly A:1, A:3, and A:4) is highly correlated to disease predilection for strains associated with fowl cholera (105,(224)(225)(226)(227), although capsular serotypes F and D have also been reported (123,124,227,228). Serotype B:3 is often isolated from avian disease cases that manifest as sinusitis (229,230) with symptoms of nasal discharge, increased lacrimation, swelling, and inflammation.…”
Section: Pasteurellosis and Fowl Choleramentioning
confidence: 99%
“…4) and has been used as a basis for serotyping (106,118). As a consequence, the cap loci of previously untyped P. multocida strains can now be subtyped based on clustering with the corresponding loci of known serotypes (118,(123)(124)(125).…”
Section: Detection Identification and Typing Of P Multocidamentioning
confidence: 99%
See 1 more Smart Citation
“…Debilitated birds take higher risks while foraging, which improves their chances of getting caught or injured (Wobeser, 2006). Interpretation of the results is further complicated, as mycoplasma in diseased birds are often found together with other pathogenic organisms (Bezjian & Bezjian, 2014;Pennycott et al, 2005;Strugnell et al, 2011). The mycoplasma in these cases could therefore be the primary cause, co-infection, secondary infection or an incidental finding.…”
mentioning
confidence: 99%